Political Influence on the Management and Financing of the Lithuanian National Radio and Television: Shifts and Consequences - Jastramskis, Deimantas (Politologija, 2018)
[only abstract in English; full article and abstract in Lithuanian]The aim of this article is to find out whether the structural conditions for an effective activity of the public broadcaster were created in Lithuania. The legal regulation of management and financing of the Lithuanian public broadcaster (LRT) are analyzed. The article also explores what political and economic circumstances were decisive in the media policy process regarding the change of the structural conditions for the effectiveness of the LRT. It is claimed in the article that the structural conditions for the effective activity of the LRT were only partially created during the 27 years of statehood. First, the model of formation of the LRT Council balanced the political representation between the LRT Council members that are delegated by three sides: the governing coalition, the opposition of the Seimas and the President. However, such regulation does not decouple the LRT’s management from any concrete political conjuncture and from any possible political coalitions in the LRT Council. Second, since 2015, the funding of LRT has been related to the revenues of the state and municipalities’ budgets (1.5 percent from the income tax and 1.3 percent from the excise revenues). However, such a financing model of the LRT is not sufficient to exclude it from the level of the least financed public service media outlets in the European Union.
Keywords: none